The Effects of Home Language and Bilingualism on the Realization of Lexical Stress in Welsh and Welsh English - Mennen, Ineke; Kelly, Niamh; Mayr, Robert; Morris, Jonathan (Frontiers in Psychology, 2020)
This study investigates effects of long-term language contact and individual linguistic experience on the realisation of lexical stress correlates in Welsh and Welsh English. To this end, a production study was carried out in which participants were asked to read out Welsh and English bisyllabic words with stress on the penultimate syllable, placed within carrier phrases. Recordings were made of the productions of Welsh and English target words, by two groups of Welsh-English bilinguals differing in home language, as well as the productions of English target words by Welsh English monolinguals and speakers of Southern Standard British English (SSBE). Acoustic measures were taken of fundamental frequency (f0) and intensity ratios of stressed and unstressed vowels, duration of stressed and unstressed vowels, and duration of the post-stress consonant. The results of acoustic comparisons of Welsh English with SSBE and Welsh revealed that SSBE differs from the other groups in all measures of lexical stress. Welsh and Welsh English, however, show considerable phonetic overlap, albeit with language-specific differences in two of the five measures (unstressed vowel duration, intensity ratio). These findings suggest cross-language convergence in the realisation of lexical stress in Welsh and Welsh English bisyllabic words with penultimate stress. Individual linguistic experience, in turn, did not play a major role in the realisation of lexical stress in these words. Bilinguals did not differ from monolinguals when speaking English, and home language also had no effect on any measure. This suggests that other factors must be responsible for the observed patterns. We discuss the possibility that the varieties of Welsh and Welsh English spoken in this community function as a sign of regional or peer group identity, rather than as markers of linguistic experience.